Regulating charitable organizations in Malaysia: a case law analysis of the BALKIS case / Zuraidah Haji Ali - Haji Ali, Dr. Zuraidah (2014)
The concept of charity in Malaysia bears no difference with the ones administered under the English Law. Despite the non- exhaustive list of charitable purposes, these purposes can basically be classified to four, namely, the relief of poverty, the advancement of education, the advancement of religion and lastly other purposes beneficial to the community. The courts and the Charity Commissioners will help to enforce charitable purposes and prevent abuse through trust law. Unlike England, there is neither specific legislation nor a proper body that focus on monitoring charitable organizations in Malaysia. Major concern such as whether money or property donated by the public has been used appropriately for charity is left unattended and unmonitored. This concern was illustrated by the BALKIS ( Badan Amal dan Kebajikan Isteri-Isteri Selangor)‟s case, whereby the changes of government in Selangor has prompted a registered society, BALKIS which is charitable in nature to dissolve itself and transferred its funds to another organization. In this case, there are few legal issues which are discussed; focusing on integrity, honesty and accountability of BALKIS (the charitable organization) that was set up under the Societies Act 1966. This paper will discuss the overall legal framework and establishment of charitable organization in Malaysia. A special reference is made on the Balkis case ( Kerajaan Negeri Selangor & Ors v Pendaftar Pertubuhan Malaysia and another suit [2012] 3 MLJ 795) where the Federal Court highlighted the issues and effect of unregulated charitable organization